PROXIMATE ANALYSIS AND MINERAL COMPONENTS OF SOME EDIBLE MEDICINALLY IMPORTANT LEAFY VEGETABLES OF KAMRUP DISTRICT OF ASSAM, INDIA - POBI GOGOI; J.C. KALITA (International Journal of Pharma and Bio Sciences, 2014)
The present study was conducted to evaluate nutritional properties of certain traditional medicinally important edible leafy vegetables of Assam, India. Nutritive value and mineral composition of Alternanthera sessilis, Drymaria cordata, Eclipta alba, Houttuynia cordata and Leucas plukenetii, which are basically used as medicine of different ailments, were determined. Proximate analysis revealed high amount of carbohydrate content ranged from 38.46-66.54%. Moisture content was found to be highest in Eclipta alba (89.1%) while protein was higher in Houttuynia cordata (19.68%). Fat content was relatively less and fiber content ranged from 9.4 - 23.52%. These vegetables were found to be rich sources of macroelements as well as trace minerals. Potassium was the most abundant macroelement ranging from 6240.0-14570.0 mg/kg, followed by sodium, calcium and magnesium. Among the trace elements Iron was highest (252.8-712.9mg/kg), followed by zinc, manganese and Copper. The results demonstrated that these 5 selected underutilized medicinal plants have great nutritional significance.